Hybrid (laparoscopy + stent) treatment of celiac trunk compression syndrome (Dunbar syndrome, median arcuate ligament syndrome (MALS)) - Maciej Michalik; Natalia Dowgiałło-Wnukiewicz; Paweł Lech; Kaja Majda; Piotr Gutowski (Videosurgery and Other Miniinvasive Techniques)
Introduction : Celiac trunk (CT) compression syndrome caused by the median arcuate ligament (MAL) is a rarely diagnosed disease because of its nonspecific symptoms, which cause a delay in the correct diagnosis. Intestinal ischemia occurs, which causes symptoms of abdominal angina. One method of treatment for this disease is surgical release of the CT – the intersection of the MAL. Laparoscopy is the first step of the hybrid technique combined with percutaneous angioplasty and stenting of the CT. Aim: To demonstrate the usefulness and advantages of the laparoscopic approach in the treatment of Dunbar syndrome. Material and methods : Between 2013 and 2016 in the General and Minimally Invasive Surgery Department of the Medical Sciences Faculty of the University of Warmia and Mazury in Olsztyn, 6 laparoscopic procedures were performed because of median arcuate ligament syndrome. During the laparoscopy the MAL was cut with a harmonic scalpel. One month after laparoscopy 5 patients had Doppler percutaneous angioplasty of the CT with stent implantation in the Vascular Surgery Department in Pomeranian Medical University in Szczecin. Results : In one case, there was a conversion of laparoscopic surgery to open due to unmanageable intraoperative bleeding. In one case, postoperative ultrasound examination of the abdominal cavity demonstrated the presence of a large hematoma in the retroperitoneal space. All patients reported relief of symptoms in the first days after the operation. Conclusions : The hybrid method, combining laparoscopy and angioplasty, seems to be a long-term solution, which increases the comfort of the patient, brings the opportunity for normal functioning and minimizes the risk of restenosis.